Rethinking institutional repositories - TAY, Chee Hsien Aaron (ZHENG Zhixian) (Institutional Knowledge at Singapore Management University, 2017)
The article discusses the reason behind the reluctance of some researchers to deposit their work in institutional repositories (IR). These include ignorance on the existence of IR and the right of researchers to self-archive, lack of permanent institutional affiliation, and the tendency of IR to offer poor user experience. Also mentioned is the need aggregate each IR and the advantage of IR over centralized silos.